Impact of COVID-19 Pandemic on Emergency Department Referrals with Urologic Complaints; a Retrospective Cross-Sectional Study - Ansari Djafari, Anahita; Javanmard, Babak; Rahavian, Amirhossein; Rafiezadeh, Ahmad Reza Rafiezadeh; Borumandnia, Nasrin; Hojjati, Seyyed Ali; Hosseininia, Seyyed Mohammad; Karami, Hormoz (Archives of Academic Emergency Medicine, 2022)
Introduction: Medical and surgical priorities were dramatically changed during the COVID-19 pandemic. This study aimed to evaluate the impact of this pandemic on presentation to emergency department (ED) with urologic complaint. Method: This cross-sectional study was conducted at a tertiary urology referral center in Tehran, Iran. The data of all ED admissions were collected and the frequency of admissions with urologic complain and their outcomes were compared between two 90-day periods (before and during COVID-19 era). Results: 480 ED admissions were studied. The number of patients visiting the ED with urologic complaint during COVID-19 era was significantly lower than the same period in the pre-COVID-19 period (125 vs. 355 admissions; p = 0.01). The mean hospitalization days for patients in the pre-COVID-19 period were significantly higher (5.6 ± 4.4 vs. 3.2 ± 4.2 days; p <0.001). The most common patient complaints before and during COVID-19 period were flank pain (32.7%) and gross hematuria (32.8%), respectively. The number of patients discharged against medical advice in the COVID-19 period was significantly higher than before (22 (17.6%) vs. 10(2.8%); p < 0.001). The number of patients who developed severe complications was significantly higher in the COVID-19 period than in the pre-COVID-19 period (p = 0.001). Conclusion: During the COVID-19 pandemic we were faced with decreasing frequency of admission with urologic complaint, change in the pattern of referrals, decrease in the duration of hospitalization, increase in the number of patients discharged against medical advice, and increase in the number of cases with irreversible urologic complications or complications requiring surgery due to deferred treatment.